Detailed Phytochemical Analysis of High- and Low Artemisinin-Producing Chemotypes of Artemisia annua - Czechowski, Tomasz; Larson, Tony R.; Catania, Theresa M.; Harvey, David; Wei, Cenxi; Essome, Michel; Brown, Geoffrey D.; Graham, Ian A. (Frontiers in Plant Science, 2018)
Chemical derivatives of aArtemisinin, a sesquiterpene lactone produced by Artemisia annua, is are the active ingredient in the most effective treatment for malaria. Comprehensive phytochemical analysis of two contrasting chemotypes of A. annua resulted in the characterisation of over 80 natural products by NMR, more than 20 of which are novel and described here for the first time. Analysis of high- and low-artemisinin producing (HAP and LAP) chemotypes of A. annua confirmed the latter to have a low level of DBR2 (artemisinic aldehyde Δ11 (13) reductase) gene expression. Here we show that the LAP chemotype accumulates high levels of artemisinic acid, arteannuin B, epi-deoxyarteannuin B and other amorpha-4,11-diene derived sesquiterpenes which are unsaturated at the 11,13-position. By contrast, the HAP chemotype is rich in sesquiterpenes saturated at the 11,13-position (dihydroartemisinic acid, artemisinin and dihydro-epi-deoxyarteannunin B), which is consistent with higher expression levels of DBR2, and also with the presence of a HAP-chemotype version of CYP71AV1 (amorpha-4,11-diene C-12 oxidase). Our results indicate that the conversion steps from artemisinic acid to arteannuin B, epi-deoxyarteannuin B and artemisitene in the LAP chemotype are non-enzymatic and parallel the non-enzymatic conversion of DHAA to artemisinin and dihyro-epi-deoxyarteannuin B in the HAP chemotype. Interestingly, artemisinic acid in the LAP chemotype preferentially converts to arteannuin B rather than the endoperoxide bridge containing artemisitene. In contrast, in the HAP chemotype, DHAA preferentially converts to artemisinin. Broader metabolomic and transcriptomic profiling revealed significantly different terpenoid profiles and related terpenoid gene expression in these two morphologically distinct chemotypes.